Chronic Calcific Pancreatitis: A Case Report from Chennai, India - Kirthika, R.; Keshavini, S.; Muppa, Leena (Journal of Pharmacy Practice and Community Medicine, 2026)
Diabetes Mellitus (DM) encompasses a spectrum of metabolic disorders, with Type 3c DM, also known as pancreatogenic diabetes mellitus, arising secondary to pancreatic disease. This abstract provides an overview of the diagnostic challenges, clinical features, pathophysiology, and management of Type 3c DM, emphasizing the importance of accurate diagnosis and tailored treatment strategies. Despite its prevalence, Type 3c DM remains significantly underdiagnosed due to overlapping symptoms with type I and Type II DM, complicating the differentiation process. Key diagnostic criteria include evidence of exocrine pancreatic insufficiency, pathological pancreatic imaging, absence of Type I DM-associated autoimmune markers, impaired beta cell function, and reduced incretin secretion. Imaging modalities such as endoscopy, MRI, and ultrasound aid in distinguishing Type 3c DM from other types. Management strategies focus on correcting both exocrine and endocrine pancreatic insufficiency, with insulin therapy serving as a cornerstone. Metformin emerges as a promising first-line therapy, while newer incretin-based agents are contraindicated due to potential pancreatic damage. Patients with Type 3c DM are prone to malabsorption, necessitating pancreatic enzyme and vitamin supplements. Dietary modifications, including a high-fiber, low-fat diet, are recommended to alleviate symptoms and prevent complications. Early detection and tailored management are crucial in reducing the morbidity and mortality associated with Type 3c DM, highlighting the importance of accurate history-taking, appropriate diagnostic tests, and recognition of various risk factors. Standardizing diagnostic criteria and increasing awareness among healthcare providers are essential steps toward improving the diagnosis and management of this often-overlooked form of diabetes mellitus.
Keywords: Type 3c diabetes; Diabetes mellitus; Chronic pancreatitis; Pancreatogenic diabetes mellitus; Exocrine pancreatic insufficiency